Library Digital Transformation: Legal and Ethical Analysis of Librarians' Use of AI to Improve Scientific Literacy - Ismiatun, Ismiatun; Sukartini, Emy (Brawijaya University Library, 2024)
The digital transformation in modern libraries employs Artificial Intelligence (AI) to enhance scientific literacy. However, the implementation of AI presents various legal and ethical challenges that must be addressed to ensure its responsible and fair use. This study utilizes a narrative literature review method, analyzing and synthesizing various relevant sources. This method is flexible, covering diverse types of literature, and is useful for developing theoretical or conceptual models. Regulations for AI in Indonesia are still incomplete, although some aspects are regulated by existing laws. Key challenges include privacy, bias, discrimination, and AI regulation. Ethical principles such as transparency, honesty, and accountability are crucial in AI utilization. Ethical guidelines and regulations must be implemented to ensure fairness and accountability. Librarians play a vital role in enhancing users' scientific literacy through training and digital resource curation. AI implementation can improve library service efficiency and quality but also requires careful attention to ethical and privacy issues. AI holds significant potential for enhancing scientific literacy and operational efficiency in libraries, but the existing legal and ethical challenges must be addressed seriously. More specific regulations and clear ethical guidelines are essential to ensure the safe and responsible application of AI. The application of AI in libraries can significantly enhance scientific literacy and service efficiency, but stricter regulations and the implementation of ethical guidelines are needed to address the existing legal and ethical challenges. This study provides guidance for libraries in adopting AI technology safely and ethically.